VISITOR’S PERCEPTIONS OF THE PRESENCE OF THE PEBUINGAN PRABUMULIH CITY FOREST, PANGKUL VILLAGE, CAMBAI DISTRICT, PRABUMULIH CITY, SOUTH SUMATERA PROVINCE - Rosianty, S.Hut, M.Si, Yuli; Heripan, Herpian; Purba, Vita Sari (Sylva Jurnal Ilmu-ilmu Kehutanan, 2023)
The management of urban forests is for the preservation, harmony and balance of urban ecosystems which include environmental, social and cultural elements. The existence of urban forests is considered important to balance activities in urban areas. The Government of Prabumulih City determines the City Forest in accordance with the Decree of the Mayor of Prabumulih No. 202/KPTS/PERTA/2010 concerning the designation of the location of the urban forest, Prabumulih City has an urban forest of ± 10 Ha in Pangkul Village, Cambai District, Prabumulih City.This research was conducted to find out the perception of visitors to the existence of the Pebuingan Prabumulih City Forest, Pangkul Village, Cambai District, Prabumulih City and find out the factors that influence visitor’s perceptions of the existence of the Pebuingan Prabumulih City Forest. This research was carried out in the Pebuingan Prabumulih City Forest from June to July 2021. The research method used is a survey method with a qualitative approach and the object of research is that visitors come to the Pebuingan Prabumulih City Forest for certain purposes or with unintentional purposes. The data collection method used in research was direct observation and interviews with respondents by using previously prepared questionnaires and data obtained from related institutions.The data processing method used was descriptive qualitative analysis, then used a Likert scale in its calculations.The results showed that visitor’s perceptions of the existence of the Pebuingan Prabumulih City Forest, Pangkul Village, Cambai District, Prabumulih City were included in very good criteria that can be seen from the level of measurement of the score of visitors' perceptions of the existence of the Pebuingan Prabumulih City Forest as seen from the ecological, aesthetic, social and economic functions with a percentage of 88.60%.